Fascia iliaca compartment block can reduce the incidence of early post-operative cognitive impairment in elderly patients with high-risk hip replacement - Tang, Li; Li, Bo; Guo, Shun; Zhao, Xiaoyong; He, Binbin; Liu, Weiwei; Xia, Rui (Frontiers in Aging Neuroscience, 2022)
Objective In this study, we aimed to observe the effects of ultrasound-guided fascia iliaca compartment block (FICB) combined with hypobaric spinal anesthesia on post-operative pain and cognitive function in elderly patients with high-risk hip replacement. Methods A total of 84 elderly patients—aged 65–85 years, with American Society of Anesthesiologists physical status III–IV, and scheduled for hip arthroplasty between September 2021 and May 2022—were selected. One or more organs with moderate to severe impairment were included in all patients. The patients were randomly divided into a hypobaric spinal anesthesia group (group C, control group) and an ultrasound-guided FICB combined with hypobaric spinal anesthesia group (group E, experimental group). Group C was given 3.5 mL of 0.32% ropivacaine hypobaric spinal anesthesia, and group E received ultrasound-guided FICB combined with 3.5 mL of 0.32% ropivacaine hypobaric spinal anesthesia. The patients were compared using the visual analog scale (VAS) for pain, Harris hip function score, and simple Mini-Mental State Examination (MMSE) scale. Blood β-amyloid (Aβ) and neuronal microtubule-associated protein (tau) levels were measured. We compared intraoperative conditions and post-operative complications between the two groups to assess the effects of FICB combined with hypobaric spinal anesthesia on post-operative pain and cognitive function in elderly patients with high-risk hip replacement. Results At 1 and 3 days after the operation, patients in group C had significantly higher VAS and lower MMES scores than those in group E. The differences were statistically significant at 1 (P < 0.01) and 3 (P < 0.05) days after the operation. At 1 day after operation, the Harris score of patients in group C was significantly lower than that of patients in group E (P < 0.05). The Aβ and tau levels of patients in group C were significantly higher than those of patients in group E at 1 day after the operation (P < 0.01). The Aβ levels of patients in group C were significantly higher than those of patients in group E at 3 days after the operation (P < 0.05). The intraoperative conditions and post-operative complication rates did not differ significantly between the two groups. At 1 day before and 5 days after the operation, there was no difference in any of the indicators. Conclusion By lowering pain and managing Aβ and tau protein concentrations, FICB can successfully lower the incidence of early post-operative cognitive impairment in elderly patients with high-risk hip replacement. Clinical trial registration www.chictr.org.cn, identifier: ChiCTR2100051162.